Television is the Face of the Nation - Rasulova Zuftuna Muradovna (International Journal on Integrated Education, 2022)
In a modern democracy, every citizen has the right to be informed about different information in the society to which he or she belongs and has freedom of speech. This, in turn, ensures a diversity of opinions in the sphere of public consciousness. The journalist has a responsibility to meet the ethical requirements of this process. This topic will be discussed in this article.